Perancangan Sistem Solar Panel Tracker Menyesuaikan Kondisi Pancaran Sinar Matahari - Muhammad Syahrul Rizal; Rohman; Jatira; Choirul Anwar; Yadi Heryadi; Irwan Suriaman (Sekolah Tinggi Teknologi Wastukancana, 2026)
Solar energy is one of the most promising and inexhaustible sources of renewable energy. Solar panels, as the primary devices for converting solar energy into electrical energy, have been widely utilized. However, issues related to the efficiency of these panels remain. Panels installed in a fixed position can only optimally absorb sunlight at a specific time of day, whereas the sun’s position shifts dynamically from east to west throughout the day. This study discusses an effective and efficient solar tracker mechanism that enables the panel to follow the sun’s movement throughout the day. The results of the study indicate that the design of a single axis solar tracker mechanism (east to west) with a target rotation of 180° over 12 hours or 15° per hourincrements requires a DC motor with a speed of 1400 rpm, an internal gearbox with a ratio of 80:1, and an external gear with a ratio of 12:1, resulting in a total gear ratio of 960:1. Consequently, the final output speed of the motor is reduced to 1458 rpm, meaning the motor only needs to be active for approximately 10.26 seconds to rotate the panel by 15° per hour.